2015
DOI: 10.1371/journal.pone.0142060
|View full text |Cite
|
Sign up to set email alerts
|

The Contributions of Segmental and Suprasegmental Information in Reading Chinese Characters Aloud

Abstract: The Chinese writing system provides an excellent case for testing the contribution of segmental and suprasegmental information in reading words aloud within the same language. In logographic Chinese characters, neither segmental nor tonal information is explicitly represented, whereas in Pinyin, an alphabetic transcription of the character, both are explicitly represented. Two primed naming experiments were conducted in which the targets were always written characters. When logographic characters served as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 54 publications
(83 reference statements)
1
17
0
Order By: Relevance
“…Although both segmental and tonal information play an important role in lexical access, readers can process and activate these two components separately (Spinks et al, 2000). Tone seems to be represented more poorly, and plays a secondary role in lexical processing as compared to segmental information, as demonstrated in previous research on visual Chinese character recognition among skilled native adult readers, using both online and off-line experiments (e.g., Taft and Chen, 1992;Chen et al, 2002;Malins and Joanisse, 2010;Li et al, 2013;Sereno and Lee, 2015;Wang et al, 2015). For example, Sereno and Lee (2015) used an online auditory lexical decision task among native Mandarin-speaking adults and their results supported for the separate roles of tone and segmental information in Chinese word processing.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Although both segmental and tonal information play an important role in lexical access, readers can process and activate these two components separately (Spinks et al, 2000). Tone seems to be represented more poorly, and plays a secondary role in lexical processing as compared to segmental information, as demonstrated in previous research on visual Chinese character recognition among skilled native adult readers, using both online and off-line experiments (e.g., Taft and Chen, 1992;Chen et al, 2002;Malins and Joanisse, 2010;Li et al, 2013;Sereno and Lee, 2015;Wang et al, 2015). For example, Sereno and Lee (2015) used an online auditory lexical decision task among native Mandarin-speaking adults and their results supported for the separate roles of tone and segmental information in Chinese word processing.…”
Section: Introductionmentioning
confidence: 84%
“…Consistently, Chen et al (2002) found priming effects for syllablealone prime (i.e., tone differed) but no priming effects for tonealone prime (i.e., syllables differed) using an implicit priming paradigm among native adult Mandarin speakers. However, there is some evidence that segmental and tonal information may also be processed as an integral unit among native speakers in a task such as primed word naming (Wang et al, 2015) or auditory word eye-tracking (Malins and Joanisse, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the tone is tightly bound with the vowel in a Chinese syllable, then as soon as the participant can detect that the two stimuli differed in the initial consonant, further consideration of a homophony judgement may not be necessary. This would suggest that in addition to having a more robust representation, the segment may also be activated earlier than the tone in visual word recognition (see further discussion in M. Wang, Li, & Lin, ). Future research needs to include a manipulation of the onset and the rime of the associated characters or Pinyin to address more fine‐grained representation of segmental information and its relation to suprasegmental information.…”
Section: Discussionmentioning
confidence: 99%
“…Previous behavioral and electrophysiological studies have addressed the unique contribution of lexical tone to successful character recognition and reading acquisition (Li, Lin, Wang, & Jiang, 2013;Nixon, Chen, & Schiller, 2015;Pollatsek, Tan, & Rayner, 2000;Verdonschot, Lai, Chen, Tamaoka, & Schiller, 2015;Wang, Li, & Lin, 2015). For instance, proficient knowledge in lexical tone phonology of characters is associated with better reading performance in Chinese children (Shu, Peng, & McBride-Chang, 2008;Tong, Tong, & McBride-Chang, 2015).…”
Section: Introductionmentioning
confidence: 99%